217. Bang for the Buck: Lessons Learned From an Ambulatory Stewardship Pilot to Reduce Excess Antibiotic Prescribing for Adult Upper Respiratory Infections. (26th November 2018) - Mittal, Jaimie; Cowman, Kelsie; Infante, Abel; Meissner, Paul; Ansari, Asif; Nori, Priya; Ostrowsky, Belinda
Abstract: Background: Upper respiratory infections (URIs) are a source of unnecessary antibiotic use in the USA. 1 To address antibiotic overuse in our clinics, we participated in a multiphase stewardship collaborative established by the United Hospital Fund. We aimed to pilot stewardship policies for adult URIs at the Montefiore Medical Group (MMG) practices in Bronx, New York. Methods: Phase 1: evaluation of provider use of ICD-10 codes for URIs generally not requiring antibiotics at target sites (TS) with random chart abstraction validation. Phase 2: implementation of stewardship interventions (Table 1). Prescribing patterns were evaluated using electronic health record data at the end of Phase 2 comparing TS ( n = 6; two resident clinics, four nonresident clinics) to the prior year and to nontarget sites (NTS) ( n = 13). Results: There were 6, 819 visits of interest from October 2017 to February 2018 within MMG. Top three codes utilized are shown in Figure 1. TS prescribing declined postintervention and compared with NTS (Table 2). Nonresident TS participated in four interventions, and resident TS were involved in 2–3. Macrolides were the most utilized antibiotic class (Figure 2). Conclusion: We attribute the decline in prescribing at TS to the collective impact of our stewardship activities. Stewardship team driven interventions had better uptake than provider-driven initiatives. We plan to continue activities with the highest uptake and feasibility. Long-term goals include development and integration of stewardship metrics into our outpatient quality structure. Reference 1. Shapiro DJ, Hicks LA, Pavia AT, Hersh AL. Antibiotic prescribing for adults in ambulatory care in the USA, 2007–2009. J Antimicrob Chemother. 2014;69(1):234–40. Disclosures: All authors: No reported disclosures.